Agronomic Meetings as a Means of Modernization of Agriculture in Ukraine in the Early Twentieth Century (as Exemplified in Poltava Region) - Aranchiy, Valentyna; Iakymenko, Mykola; Sharavara, Tamara (Український історичний журнал, 2020)
The aim of the research is to determine the reasons, form, content and consequences of such a social phenomenon as agronomic meetings (the practice of which was quite common in the southwestern regions of the Russian Empire in the early 20th century, in particular in Poltava region) for the socio-economic development of the country. The research methodology is based on the principles of scientificity, historicism, authors’ objectivity, regionalism, as well as the use of general scientific methods such as analysis and synthesis, induction and deduction and specific historical ones, namely, historicalgenetic, historical-comparative and historical-systemic methods. The scientific novelty of the research is characterized by the fact that on the basis of the analysis of little-known historical sources, the authors for the first time in national historiography have analyzed the publications of Poltava provincial zemstvo, as well as publications of local agricultural societies, including magazines "Khutorianyn" and "Bulletin of South Russian Animal Husbandry" in terms of the content and consequences of agronomic meetings set up by local public activists aimed at the modernization of agricultural production, which was particularly topical during the implementation of Stolypin’s agrarian reform. The importance of the mentioned meetings was: to involve a wide range of people relating to the agrarian sector in the discussion, among them were not only practitioners, but also well-known theorists from university professors; to disseminate the ideas formulated during the relevant meetings in media, in the process of consultations provided by local agronomists, lectures and conversations with the illiterate population. Along with the analysis of the content of agronomic meetings, the authors paid attention to their socioeconomic reasons and consequences, which, above all, enables to understand this process in a holistic way, taking into account all the circumstances that directly or indirectly affected the meetings held by the local agricultural society and Poltava provincial zemstvo. Conclusions. As a result of the research, it was concluded that such a method of the modernization of crop production and animal husbandry as agronomic meetings with participation of not only public figures from among local agricultural societies and zemstvo figures, but also representatives of central authorities of Poltava province.